Comparing the Contributions of Acute and Postacute Care Facility Characteristics to Outcomes After Hospitalization for Hip Fracture. Issue 4 (April 2017) - Neuman, Mark D.; Silber, Jeffrey H.; Passarella, Molly R.; Werner, Rachel M.
Abstract : Objective: To quantify the contribution of acute versus postacute care factors to survival and functional outcomes after hip fracture. Design, Setting, and Participants: Retrospective cohort study using Medicare data; subjects included previously ambulatory nursing home residents hospitalized for hip fracture between 2005 and 2009. Methods: We used logistic regression to measure the associations of hospital and nursing home factors with functional and survival outcomes at 30 and 180 days among patients discharged to a nursing facility; we quantified the contribution of hospital versus nursing home factors to outcomes by the ω statistic. Results: Among 45, 996 hospitalized patients, 1814 (3.9%) died during hospitalization. A total of 42, 781 (93%) were discharged alive to a nursing home. Of these, 12, 126 (28%) died within 180 days and 20, 479 (48%) died or were newly unable to walk within 180 days. Hospital characteristics were not consistently associated with outcomes. Multiple nursing home characteristics predicted 30- and 180-day outcomes, including bed count, chain membership, and performance on selected quality measures. Nursing home factors explained 3 times more variation in the odds of 30-day mortality than did hospital factors [ω, hospital vs. nursing home: 0.32; 95% confidence interval (CI), 0.11, 0.96], 7 times more variation in the odds of 180-day mortality (ω: 0.15; 95% CI, 0.04, 0.61), and 8 times more variation in the odds of 180-day death or new dependence in locomotion (ω: 0.12; 95% CI, 0.05, 0.31). Conclusions: Nursing home factors explain a larger proportion of the variation in clinical outcomes following hip fracture than do hospital factors. Abstract : Supplemental Digital Content is available in the text.